1994
DOI: 10.1007/bf00007974
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of soil fractions and location of soil bacteria in a vertisol under cultivation and perennial grass

Abstract: Effects of soil management on soil characteristics were investigated on the rhizosphere (RPP) and the nonrhizosphere (NRPP) soil of a re-grass vertisol under Digitaria decumbens and in the soil under continuous cultivation (CC). A low energy technique allowed to separate eight size and density fractions, including macro-and microaggregates while preserving soil bacteria. Organic C and N, microbial biomass C and the number of total bacteria (AODC) and of Azospirillum brasilense and their distribution were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 36 publications
(32 reference statements)
0
23
0
Order By: Relevance
“…5) revealed that most differences in genetic structure occurred between the coarse fractions (Ͼ250 m and 50 to 250 m) and the clay fraction (Ͻ2 m). Various studies, such as whole-cell counting (24,40) and biomass measurements (23), as well as specific bacterial enumerations (25) and determinations of the genetic structures (40) and activities (6,28,30) of bacterial subcommunities, have shown that soil microenvironments differ from each other. Ordering on PC1 grouped nifH gene pools located in microenvironments with similar granulometric characteristics: the two coarse fractions (Ͼ250 m and 50 to 250 m) were closely related, as were the two medium fractions (20 to 50 m and 2 to 20 m).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) revealed that most differences in genetic structure occurred between the coarse fractions (Ͼ250 m and 50 to 250 m) and the clay fraction (Ͻ2 m). Various studies, such as whole-cell counting (24,40) and biomass measurements (23), as well as specific bacterial enumerations (25) and determinations of the genetic structures (40) and activities (6,28,30) of bacterial subcommunities, have shown that soil microenvironments differ from each other. Ordering on PC1 grouped nifH gene pools located in microenvironments with similar granulometric characteristics: the two coarse fractions (Ͼ250 m and 50 to 250 m) were closely related, as were the two medium fractions (20 to 50 m and 2 to 20 m).…”
Section: Discussionmentioning
confidence: 99%
“…The cultivated LCSA-c soil sample was separated into five fractions, corresponding to various sizes of particles and aggregates, by a size fractionation procedure (25). The 250-to 2,000-m and 50-to 250-m fractions were coarse and fine sands, respectively, with associated macroaggregates.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter respect, Trehen et al (1993) asked a similar question by formulating conceptual approaches in soil biology: ªWhere are the microbes located, and are there specific locations for the different microbial activities?º In our previous paper we demonstrated the feasibility of selected microbiological and biochemical soil parameters to indicate the effects of a longterm wastewater irrigation on a sandy Cambisol and Haplic Luvisol (Filip et al, 1999). Such an ecological approach to soil microbiology received recently an enhanced attention in studies published by Kabir et al (1994), Nacro et al (1996), Van Gestel et al (1996), Monreal and Kodama (1997), Chotte et al (1998) and Stemmer et al (1998). Yet, the ecologically based soil investigations require also the existing relationship between the biotic and abiotic soil constituents to be consequently elucidated (Filip, 1975;Munch 1995).…”
Section: Introductionmentioning
confidence: 93%
“…The soil was fractionated using thestandard method outlined by Kabir et al, (1994). One hundred gram soil was taken in 250ml Erlenmeyer flask containing sterile distilled water and kept at 4C for 36h.…”
Section: Soil Fractionationmentioning
confidence: 99%